2019
DOI: 10.1038/s41598-019-45033-1
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of a Central Kurdish version of the Dizziness Handicap Inventory

Abstract: We cross-culturally adapted the Dizziness Handicap Inventory (DHI) into Central Kurdish dialect (DHI − CK) and verified its reliability and validity. A cross-sectional study was utilised to measure the impacts of vestibular disorders. Along with the DHI − CK, two comparators were introduced: the Visual Analogue Scale and the Clinical Test of Sensory Interaction and Balance. External and internal reliability were tested with intraclass correlation coefficient (ICC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Eighteen studies reported on test–retest reliability of the DHI total score (Table 4) (4,20,22,26,27,30,34,35,43,46,47,49,51,53,54,57–59), with sample sizes varying from 14 (4) to 106 (20). Time between the test and retest ranged from “the same day” to “15 days.” We considered a time interval of >24 h “appropriate” and consequently rated the methodological quality of two studies as “inadequate” due to inappropriate (i.e., too short) time interval (4,20).…”
Section: Content Validitymentioning
confidence: 99%
See 3 more Smart Citations
“…Eighteen studies reported on test–retest reliability of the DHI total score (Table 4) (4,20,22,26,27,30,34,35,43,46,47,49,51,53,54,57–59), with sample sizes varying from 14 (4) to 106 (20). Time between the test and retest ranged from “the same day” to “15 days.” We considered a time interval of >24 h “appropriate” and consequently rated the methodological quality of two studies as “inadequate” due to inappropriate (i.e., too short) time interval (4,20).…”
Section: Content Validitymentioning
confidence: 99%
“…Fifteen studies reported data on construct validity (4,19,21,23,25,27,34,40,43–45,47,51,55,59) (Table 5). The methodology of the studies was rated as “adequate,” because we assumed that the measurement properties of the comparator instruments were adequate, the correlated constructs were clear, and the statistical methods appropriate.…”
Section: Content Validitymentioning
confidence: 99%
See 2 more Smart Citations
“…The critical values for coefficient ω are similar to Cronbach Alpha values. The average interitem correlation should fall between 0.15 and 0.50 (Clark and Watson, 1995;Zmnako and Chalabi, 2019). Spiliotopoulou (2009) specified that the average interitem correlation should be included "within the range of 0.15-0.20 for outcome measures that measure broad characteristics (i.e., general constructs such as extraversion) and between 0.40 and 0.50 for those tapping narrower ones (i.e., specific constructs such as talkativeness."…”
Section: Instrumentsmentioning
confidence: 99%